Acceptance of Covid-19 Vaccination: Perspectives of an Urban Community in Ghana - Anane, Akosua Asantewaa; Odum-Sackey, Bismark; Dedzo, Yvonne (Advances in Social Sciences Research Journal, 2023)
Since the start of the COVID-19 pandemic, research on the adoption and spread of the COVID-19 vaccination has been conducted all over the world. However, studies on the spread of the COVID-19 vaccine and its subsequent acceptance have received little attention in Ghana. This study investigated how the general population reacted to the Government of Ghana’s COVID-19 vaccination diffusion strategy as well as the motivating factors for its acceptance. In-depth interviews with thirty (30) purposefully selected respondents were conducted. The interview data were thematically analysed. Themes that emerged from the analysis included: conspiracy theory, vaccine as free lunch, misconception about susceptibility of COVID-19, misinformation and public education and lack of trust in the Government and the health system. The study’s findings show that reluctance to receive vaccine is a significant obstacle to establishing effective vaccination efforts during the pandemic. We conclude that conspiracy theory, vaccine as free lunch, misconception about susceptibility of COVID-19, misinformation and public education and lack of trust in the Government and the health system as factors resulting in vaccine hesitancy. The study’s conclusions can also give the Ghanaian government ideas for approaches to adopt in order to allay respondents’ worries. This may significantly lessen vaccine hesitancy among Ghanaians.